2010
DOI: 10.5657/fas.2010.13.4.300
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Inclusion of Red Ginseng Byproduct on Growth, Body Composition, Serum Chemistry, and Lysozyme Activity in Juvenile Olive Flounder (Paralichthys olivaceus)

Abstract: This study examined the effects of the dietary inclusion of various concentrations of red ginseng byproduct (RB) and a mixture containing red ginseng byproduct, garlic extract, yeast and filler (CR) on the growth, body composition, serum chemistry, and lysozyme activity of juvenile olive flounder (Paralichthys olivaceus). Juvenile fish (n = 630) weighing 5.0-g were randomly distributed into 21 180-L flow-through tanks (30 fish/tank). Seven experimental diets were prepared in triplicate: a control diet without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…All groups that received XTRACT ® extract by both doses or combined with Flumequine were significantly higher in weight gain % than group that received Flumequine alone, these agree with Choi I, et al [43], Nakagawa H, et al [12], while disagree with Sanchez-Martínez JG, et al [44]. The specific growth rate of all treated groups in our work was significantly higher than control untreated group, these results correspond with Choi I, et al [43] while disagree with Maass N, et al [45] who examined the effect of feeding oxytetracycline on the growth of catfish for 11 weeks and found that the specific growth rate showed no significant change in the oxytetracycline treated fish. Group received Echinacea extract showed a significantly higher value in comparison with other groups, these work in with Nakagawa H, et al…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…All groups that received XTRACT ® extract by both doses or combined with Flumequine were significantly higher in weight gain % than group that received Flumequine alone, these agree with Choi I, et al [43], Nakagawa H, et al [12], while disagree with Sanchez-Martínez JG, et al [44]. The specific growth rate of all treated groups in our work was significantly higher than control untreated group, these results correspond with Choi I, et al [43] while disagree with Maass N, et al [45] who examined the effect of feeding oxytetracycline on the growth of catfish for 11 weeks and found that the specific growth rate showed no significant change in the oxytetracycline treated fish. Group received Echinacea extract showed a significantly higher value in comparison with other groups, these work in with Nakagawa H, et al…”
Section: Discussionsupporting
confidence: 84%
“…[12], Kasiri M, et al [41], Goda S, [42]. The best feed utilization was for groups received XTRACT ® extract by both doses with Flumequine followed by groups received XTRACT ® extract by both doses then group received Flumequine alone and finally the control group, these findings consistent with Przybilla P, et al [46], Choi I, et al [43]. On the other hand conflict with Sanchez-Martínez JG, et al [44], Maass N, et al [45].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Choi et al . observed that red ginseng byproduct effectively improved lysozyme activity of juvenile olive flounder . However, there are very few reports on the interaction of ginsenosides and lysozyme .…”
mentioning
confidence: 99%
“…[18] Choi et al observed that red ginseng byproduct effectively improved lysozyme activity of juvenile olive flounder. [19] However, there are very few reports on the interaction of ginsenosides and lysozyme. [20,21] Previous studies by Qu et al reported the interaction of lysozyme with two protopanaxatriol-type ginsenosides (Rg 1 and Re) under harsh experimental conditions with a high content of organic solvent and acetic acid, respectively.…”
mentioning
confidence: 99%